Practical Approaches Toward Sustainable Development in Iranian Green Construction - Mohammad Reza Darabpour; Mehrab Darabpour; Javad Majrouhi Sardroud; John Smallwood; Gholamali Tabarsa (Salehan Institute of Higher Education, 2018)
Developed nations acknowledge sustainable development as a legal right for current and future generations. Although instances of domestic and international efforts are prevalent, there is a long way to go before accomplishing developmental ideals. A practical approach for realizing the vital goals of sustainable development is of the utmost importance. In effect, the construction sector requires extensive forward-looking studies for strategizing, building and granting a sustainable future. The inconsistency between the goals and activities of different sectors is a main impediment upon undertaking sustainable development’s goals; decision and lawmakers must consider the purpose and interests of the building industry on a micro and macro level. This paper is a brief review for understanding the concept of sustainable development and illustrates some of the international efforts, and highlights them for decision makers. Using the ‘PESTLE’ analysis technique, external and internal factors influencing sustainability in the Iranian construction sector were identified. Interviews were conducted with experts using the ‘Snowball’ research method due to the lack of knowledgeable respondents in the subject area. 11 Practical steps needed in Iran were recommended and sorted by their importance to make this vision a reality. The results can be generalized to other disciplines as well.